Physical and Chemical Properties of Robusta Coffee Beans at Different Temperatures and Roasting Times - Anis Nurhayati; Eko Sutrisno; Mulono Apriyanto (Open Global Scientific Journal, 2023)
Robusta coffee in the Rejosari Mojokerto Village is undertaken by the local community. However, to ensure the production of high-quality coffee and avoid the production of low-priced products, it is imperative for the community to possess a comprehensive understanding and knowledge of coffee post-harvest processing methods. This study aims to investigate the physicochemical properties of Robusta coffee under varying roasting temperatures and times. Several key variables were observed, including the number of beans per 100 grams of coffee, geometric diameter (GM), and average weight of coffee beans, which were employed to assess the physical properties of the coffee. Furthermore, the chemical composition of coffee was analyzed in terms of extract weight, ash content, caffeine, glucose, and coffee protein levels. The results indicate that 100 grams of Robusta coffee contain an average of 368 individual coffee beans, each weighing approximately 0.27 grams, with a geometric dimension (GM) of 10.3 mm. Moreover, the extract weight, caffeine, glucose, and protein content exhibit a decreasing trend during the roasting process. As the roasting time increases and the temperature rises, the percentage of coffee extract and caffeine content decreases. Notably, coffee roasted at 200°C for 20 minutes exhibits the highest ash percentage, reaching 4.16%. It was observed that higher roasting temperatures and longer roasting periods result in increased ash content. This study highlights the significant influence of varying roasting temperatures and times on the quality of the resulting coffee beverage.